Profile of Indian Children with Childhood Ataxia and Central Nervous System Hypomyelination/Vanishing White Matter Disease: A Single Center Experience from Southern India - Gowda, Vykuntaraju K.; Srinivasan, Varunvenkat M.; Nagarajan, Balamurugan; Bhat, Maya; Shivappa, Sanjay K.; Benakappa, Naveen (Journal of Pediatric Genetics, 2020)
Background Childhood ataxia with central nervous system hypomyelination (CACH) is a recently described childhood inherited white matter disease, caused by mutations in any of the five genes encoding eukaryotic translation initiation factor (eIF2B).Methods Retrospective review of the charts of children with CACH was performed from January 2014 to March 2020 at tertiary care center from Southern India. Diagnosis was based on magnetic resonance imaging (MRI) criteria or genetic testing.Results Total number of children with CACH enrolled were 18. Male/female ratio was 10:8. Mean age of presentation was 37.11 months (range =  6–144 months). Affected siblings were seen in five (28%) cases. All children had spasticity, ataxia, and diffuse white matter changes with similar signal as cerebrospinal fluid on all pulse sequences on MRI brain. Of the 18 children, only nine are alive. Duration of illness among deceased children was 9.6667 months (range = 2–16 months). Waxing and waning of symptoms were seen in seven cases. Genetic analysis of EIF2B gene was performed in five cases, among which three mutations were novel.Conclusion A diagnosis of childhood ataxia with central nervous system hypomyelination should be considered in patients presenting with acute onset neuroregression following infection or trauma with associated neuroimaging showing classical white matter findings.
Keywords: EIF2B; childhood ataxia with central hypomyelination; vanishing white matter disease